Предмет: Математика,
автор: кул7
С объяснением пожалуйста, ............ё
Приложения:
Ответы
Автор ответа:
0
z(2+i)=3-i
z = (3-i) / (2+i)
z = (3-i) * (2-i) / ((2+i)*(2-i))
z = (6 - 2i - 3i + i^2) / (2^2 - i^2)
z = (5 - 5i) / 5 = 1 - i
z = (3-i) / (2+i)
z = (3-i) * (2-i) / ((2+i)*(2-i))
z = (6 - 2i - 3i + i^2) / (2^2 - i^2)
z = (5 - 5i) / 5 = 1 - i
Похожие вопросы
Предмет: Химия,
автор: dtsaloyev
Предмет: Английский язык,
автор: sakanyanelina
Предмет: Математика,
автор: chedan12
Предмет: Физика,
автор: charodeikaalen
Предмет: Литература,
автор: 11111angry